2006
DOI: 10.1002/ajim.20323
|View full text |Cite
|
Sign up to set email alerts
|

Metal and non‐metal miners' exposure to crystalline silica, 1998–2002

Abstract: Known dust control methods should be implemented and regular medical surveillance should be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…A related concern was highlighted by Weeks and Rose, (18) who analyzed the results of all silica exposure samples taken by the Mine Safety and Health Administration (MSHA) over the 5-year period 1998-2002 in metal and nonmetal mines. In all, they identified 16,207 8-hr full-shift personal air samples that contained >1% silica by mass and also met certain quality assurance criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A related concern was highlighted by Weeks and Rose, (18) who analyzed the results of all silica exposure samples taken by the Mine Safety and Health Administration (MSHA) over the 5-year period 1998-2002 in metal and nonmetal mines. In all, they identified 16,207 8-hr full-shift personal air samples that contained >1% silica by mass and also met certain quality assurance criteria.…”
Section: Discussionmentioning
confidence: 99%
“…No cases of silicosis were found. Risk factors for silicosis in metal and non-metal miners have been enumerated by Weeks and Rose [2006]. These include latency of more than 10 years since first exposure, cumulative exposure, and exposure to freshly fractured quartz.…”
Section: Discussionmentioning
confidence: 99%
“…In the metal/nonmetal mining industry (103,327 samples) the overall geometric mean of silica exposure levels was 0.009 mg/m 3 ; 6.2% of all samples exceeded the MSHA PEL and 10.6% exceeded the NIOSH REL [National Institute for Occupational Safety and Health, 2008c]. Weeks and Rose [2006] evaluated metal/nonmetal miners' exposure to crystalline silica using 1998-2002 MSHA inspection data. The authors identified 12 jobs with more than 100 samples for which the mean exposure exceeded 0.05 mg/m 3 .…”
Section: Industry and Occupationmentioning
confidence: 99%